Enforcement of Law Against Understanding Product Businesses and Fertilizer Districts in the Framework of Realizing Food Security - Ramdania, Dini; Setiadi, Edi; Herniarti, Dini Dewi (Badamai Law Journal, 2024)
Fertilizer is an important element in agriculture besides seeds and water, so the state then stipulates SNI obligations for fertilizer products to make agricultural products a success and also to protect the nutrients contained in the soil so that they are not damaged. But in reality, it is often found in the field that there are certain parties who produce and distribute non-SNI fertilizers for personal gain. In fact, fertilizers that do not have SNI with unclear content will cause damage to the soil and recovery will take a long time. Unfortunately, criminal acts of product and distribution of non-SNI fertilizer continue to occur in different locations, as if there is no deterrent effect on the perpetrators because in several cases the production and distribution of non-SNI fertilizer only reaches the level of investigation due to lack of experts from the Ministry of Agriculture. Law no. 20 of 2014 concerning standardization and conformity assessment and other laws regulate them but are difficult to implement in the field because there must be coordination between institutions.